Social phobia among secondary school students in Babil, Iraq - Hussein, Ahmed H.; Alnasrawi, Anwer N.; Al-Hemiary, Nesif N.; Al-Diwan, Jawad K. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Social phobia is common among adolescents. It can have a negative impact on school achievement.Objctives: to study prevalence of social phobia among secondary school students and its impact on school achievement.Methods: A total of 500 secondary school students were included in the study. They were randomly chosen from 8 schools for boys and girls in Babil city. Social phobia inventory (SPIN) was used to assess the presence of social phobia, and success or failure in the past year was used as indicator for school achievement.Results: Social phobia prevalence among students was 32.4%. It was more common among females and students from rural areas. Students with social phobia had failed more frequently than those without social phobia (38.4% vs. 30%).Conclusion: Social phobia is common and has negative impact on school performance among secondary school students.